Orderly Administration of Government: Toponymy and Territorial Mapping Implementation in Sangihe Island Regency - Bataha, Katerina; Pioh, Novie Revlie; Monintja, Donald K (Universitas Muhammadiyah Gorontalo, 2023)
As a border area, Sangihe Islands Regency is interested in implementing toponymy to realize orderly government administration, protect the sovereignty and security of the territory of the Unitary State of the Republic of Indonesia, and preserve cultural, historical and customary values. This study aims to describe and describe the process of implementing toponymy and mapping areas in the Sangihe Regency, along with findings on all matters that influence the implementation of these policies to orderly government administration. This study uses a qualitative method with a case study approach. The results showed that within one year, the government, through the district toponymic work team, proposed 396 topographical names from various elements and standardized 165 topographical names while still paying attention to local wisdom. The district work team focused on collecting data and naming the outermost islands' topographical features to protect Indonesia's border areas. In its implementation, there were several obstacles related to the budget and the number of surveyors and the quality of surveyors. Therefore, the local government and district work teams must commit to providing a toponymy budget for 2023, increasing the number of surveyors and giving training to surveyors for the accuracy of topographical names in the Gazetteer of the Republic of Indonesia as a single reliable and accountable reference and to collaborate or build cross-sectoral synergies.